Analisis Penyebab Terjadinya Overcapacity Pada Gudang Menggunakan Metode Root Cause Analysis (RCA) di PT. XYZ - Bayu Dedi Saputra Budianto; Akmal Suryadi (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
PT. XYZ is a manufacturing company that assembles bicycles. The company's problem is that there is excess capacity in the warehouse owned by PT. XYZ. Overcapacity occurs when the number of incoming goods exceeds the optimal capacity of the warehouse. The purpose of this study is to identify the cause of overcapacity in the warehouse of PT. XYZ's warehouse and to find a solution to the problem in order to prevent similar incidents in the future. The method used is root cause analysis and the tools used are fishbone diagram and 5-why analysis. The results of the study using the fishbone diagram show that there are four aspects that are the root causes, namely errors in purchasing planning (man), excessive use of pallets (method), accumulation of bicycle spare parts (material), use of warehouse capacity that is not optimal (environment). Each of these aspects has a known trigger root after applying the 5-why analysis. Once the triggers of each problem are known, the preparation of corrective actions, which are solutions, is accompanied by the company's commitment to implement the solution in order to prevent problems that have the potential to recur.